New Indazole Derivatives as Potential Scaffolds for the Development of Anticancer, Antiviral, and Anti-tuberculosis Chemotherapeutic Compounds - Khandazhinskaya, Anastasia; Kondrashova, Evgenya; Sokhraneva, Vera; Novikova, Olga; Velikorodnaya, Yulia; Gorshenin, Andrey; Andreevskaya, Sofya; Smirnova, Tatiana; Moroz, Maxim; Kirillov, Ilya; Fedyakina, Irina; Chizhov, Alexandr; et al. (Current Medicinal Chemistry, 2026)
IntroductionChemotherapy remains essential despite advances in immunotherapy, radiotherapy, and biological therapy. However, the wide range of chemical drugs is limited by a narrow therapeutic index, low selectivity, and the development of resistance. In this regard, new high-efficiency drugs are in extremely high demand. The indazole moiety, a scaffold found in many biologically active compounds, was selected for use in new drug design.MethodsSix new indazole derivatives were synthesized via Suzuki-Miyaura coupling starting from bromoindazole. Their antiviral (against influenza A and SARS-CoV-2), antibacterial (against M. tuberculosis), and antiproliferative activities (against neuroblastoma, glioma, leukemia cell lines) were evaluated in vitro. Acute toxicity was assessed in mice of both sexes via single intragastric administration, with toxicometric parameters and pathomorphological changes studied.Results6-(1H-pyrazol-4-yl)-1H-indazole (8) suppressed the reproduction of the influenza virus at non-toxic doses to the MDCK cells and showed cytotoxicity against cancer cell lines, with an IC50 between 4 and 14 µM. However, it exhibited significant acute toxicity in mice (LD50 40 mg/kg), causing systemic organ damage.DiscussionDerivative 8 demonstrated promising antiviral and antiproliferative activities but exhibited considerable acute toxicity in vivo. The antiviral efficacy, although lower than oseltamivir, is meaningful and justifies further optimization and investigation. Its antibacterial activity against M. tuberculosis adds to its potential as a multifunctional agent.ConclusionWhile derivative 8 has shown potential as an antiviral and anticancer agent, its high toxicity highlights the need for further studies to define a safe and effective therapeutic window. Overall, the indazole scaffold remains a valuable platform for the development of new therapeutic compounds.
Keywords: Mycobacterium tuberculosis